Trade agreements and survival of service exports from Kenya - SocratesKraido Majune; Kamau John Gathiaka; Michael Jairo Ndwiga (Cogent Economics & Finance, 2022)
This study investigates the effect of GATS, a service-specific trade agreement, on the survival of service exports from Kenya to 176 countries between 1995 and 2019. Services are classified at a 1-digit level: travel, transport, computer and information, construction, financial, insurance, government, other business, and personal, cultural, and recreational services. The discrete-time probit model with random effects reveals that GATS reduces the survival of service exports by 0.78%. At the category level, GATS only increases the survival of construction and government services. GATS also reduces the survival of Kenya's exports to Africa when geographical regions are considered. However, GATS boosts the survival of services when it is interacted with the quality of institutions and the Services Trade Restrictiveness Index (STRI). Accordingly, reducing regulations and general improvement of the quality of institutions can help countries reap the benefits of a service-specific trade agreement fully.
Keywords: 330; trade agreements; GATS; export survival; service exports; Kenya